Polyimide/mesoporous silica nanocomposites: Characterization of mechanical and thermal properties and tribochemistry in dry sliding condition - Ma, J.; Qi, X.; Zhao, Y.; Dong, Yu; Song, L.; Zhang, Q.; Yang, Y. (Elsevier, 2016)
Mesoporous silica (MPS) with tunable mesopore channels can be used to reinforce polymers and has great potential in tribological applications, which is rarely investigated by research community. In this study, comprehensive properties of polyimide (PI)/MPS nanocomposites were investigated. The results demonstrated a slightly decreased tensile strength but increased modulus, microhardness and thermal stability of the PI/MPS nanocomposites. In particular, tribological properties of PI/MPS nanocomposites as functions of MPS content, applied load and sliding speed were systematically investigated. The incorporation of 1.5 wt.% MPS increased the anti-wear resistance of PI by more than 14-fold while the coefficient of friction decreased by 27%. This was highly associated with the formation of high-quality transfer film on the bearing steel counterpart surface.Relevant tribochemistry was thoroughly revealed by X-ray photoelectron spectroscopy (XPS) analysis on the transfer film and Raman analysis on the worn surfaces. This study confirmed the high efficiency of using MPS to reinforce PI polymer for tribological applications and elaborated tribochemistry to further understand the tribochemical process in polymer-metal rubbing systems.